Antiophidic Solanidane Steroidal Alkaloids from Solanum campaniforme - Torres, Maria Conceicao M.; Pinto, Francisco das Chagas L.; Braz-Filho, Raimundo; Silveira, Edilberto R.; Pessoa, Otilia Deusdenia L.; Jorge, Roberta Jeane Bezerra; Ximenes, Rafael Matos; Azul Monteiro, Helena Serra; Azul Monteiro Evangelista, Janaina Serra; Diz-Filho, Eduardo B. S.; Toyama, Marcos Hikari [UNESP] (Amer Chemical Soc, 2011)
Three new solanidane alkaloids bearing a 22,23-epoxy ring (1-3) and four known compounds were isolated from leaves of Solanum campaniforme. The structures were determined using spectroscopic techniques, including ID and 2D NMR, and HRESIMS experiments. The antiophidic activity of the alkaloids was tested against Bothrops pauloensis venom. Compounds 1-3 completely inhibited myotoxicity without inhibiting phospholipase A(2) activity of the venom, while hemorrhage and skin necrosis were significantly reduced in the presence of alkaloids 1 and 2.